2022
DOI: 10.3390/land11101852
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Driving Factors of Basin Ecosystem Service Value Based on Local Bivariate Spatial Correlation Patterns

Abstract: Ecosystem service value (ESV) is a crucial indicator for evaluating ecosystem health, and identifying its spatial driving factors will help to provide scientific decision support for ecological protection and restoration. This study took the Liuxi River Basin in China as the research object and used the value equivalent method to estimate regional ESV. In the process of using the Geodetector model (GDM), the study area was spatially stratified by using the local bivariate spatial correlation pattern to mine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Therefore, if Pearson parametric correlation test is applied, the trade-off or synergy relationship between these two, such as the relationship of one increase and one decrease contains the two opposite situations of the best and the worst, can not be accurately assessed. So, this paper uses the bivariate spatial auto-correlation analysis ( (8) , (9) ) [ 42 , 43 ] to present the trade-off-synergy relationships between ANCE and ESAP. According to the conclusion of Zhang et al (2022) [ 31 ] on the decoupling relationship between agricultural carbon emission reduction and agricultural product supply guarantee, the classification of area can be divided into low-low agglomeration trade-off zone, low-high agglomeration synergy zone, non-significant zone, high-low agglomeration non-trade-off-synergy zone and high-high agglomeration trade-off zone.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, if Pearson parametric correlation test is applied, the trade-off or synergy relationship between these two, such as the relationship of one increase and one decrease contains the two opposite situations of the best and the worst, can not be accurately assessed. So, this paper uses the bivariate spatial auto-correlation analysis ( (8) , (9) ) [ 42 , 43 ] to present the trade-off-synergy relationships between ANCE and ESAP. According to the conclusion of Zhang et al (2022) [ 31 ] on the decoupling relationship between agricultural carbon emission reduction and agricultural product supply guarantee, the classification of area can be divided into low-low agglomeration trade-off zone, low-high agglomeration synergy zone, non-significant zone, high-low agglomeration non-trade-off-synergy zone and high-high agglomeration trade-off zone.…”
Section: Methodsmentioning
confidence: 99%
“…The calculations were performed using GeoDa 1.20 software, and the geographic weight matrix used was based on the first-order queen or rook contiguity. The formulas [60][61][62][63] are as follows:…”
Section: Spatial Autocorrelation Analysismentioning
confidence: 99%
“…Through spatial autocorrelation modeling, Huang et al [49] analyzed the relationship between influencing factors, such as the intensity of human activities in the Three Gorges Reservoir area, and the landscape pattern and found that the distance was the key influencing factor affecting the evolution of the ecosystem. Ding et al [50] used a hierarchical approach of bivariate spatial autocorrelation to study the spatial autocorrelation and spatial heterogeneity of the Liuxi River, effectively capturing the spatial explanatory power of the drivers. In Henan Province, the topography is complex, stretching from the rugged mountains and hills in the west to the expansive plains in the east.…”
Section: Introductionmentioning
confidence: 99%